State of health and efficiency of rehabilitation of Tomsk people subjected to the action of radiation during the liquidation of technogenic accidents and disasters - L. V. Kapilevich; M. A. Vnushinskaya (Бюллетень сибирской медицины, 2010)
The investigation of the state of health of Tomsk people subjected to the action of radiation during the liquidation of technogenic accidents and disasters has revealed the progressing worsening of the health. Some peculiarities of the morbidity, invalidization, and mortality have been noted. An important aspect of the health improvement is the development and realization of individual rehabilitation programs.